Socialization on the Use of the School Activity and Budget Plan Application (ARKAS) for PAUD School Principals in Sentani District, Jayapura Regency - Labobar, Bernard; Wangguway, Yustinus; Tasijawa, Riski; Abineno, Fransina O; Sokoy, Mieke (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to investigate the impact of socialization on the use of the School Activity Plan and Budget Application (ARKAS) for PAUD principals in Sentani District, Jayapura Regency. Socialization methods included intensive training in the use of ARKAS for budget planning, activity monitoring, and school financial reporting. Data was collected through direct observation and interviews with socialization participants. The results showed significant improvements in principals' understanding and skills in using ARKAS, as well as improvements in the efficiency of school budget management. The conclusion of this study is that the implementation of ARKAS effectively supports transparency and accountability in the management of PAUD school funds, with positive implications for the quality of education in Sentani District. The study recommends widespread implementation of ARKAS in PAUD schools as a step towards more structured and efficient education management.